1988
DOI: 10.1128/aac.32.8.1204
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nanoparticle-bound ampicillin in the treatment of Listeria monocytogenes infection in athymic nude mice

Abstract: The effectiveness of nanoparticle-bound ampicillin was tested in the treatment of experimental Listeria monocytogenes infection in congenitally athymic nude mice. Nanoparticles of polyisohexylcyanoacrylate (PIHCA) 187 13 nm in diameter were bound to ampicillin at an ampicillin/PIHCA ratio of 0.2:1. The proportion of ampicillin bound was 90% + 3%. After adsorption onto nanoparticles, the therapeutic activity of ampicillin increased dramatically over that in the free state. Thus, 2.4 mg of nanoparticle-bound amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
1
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 15 publications
2
31
1
2
Order By: Relevance
“…At day 19 after challenge, the same differences in the hepatic counts were observed whereas splenic counts were not significantly different between the various groups of mice. This effect was greater than that observed previously in the spleen and liver after the injection of free ampicillin (9) and was more pronounced in the spleen than that observed previously after treatment with ampicillin bound to PIHCA nanoparticles (9). Our liposomal preparation was also more effective than the preparation described by others (2), which, in the same experimental model, had no effect on bacterial counts, presumably, as stated above, because a smaller amount of liposome-entrapped ampicillin was injected into the mice (2 doses of 0.27 mg each versus 3 doses of 0.8 mg each in the present study).…”
contrasting
confidence: 47%
See 2 more Smart Citations
“…At day 19 after challenge, the same differences in the hepatic counts were observed whereas splenic counts were not significantly different between the various groups of mice. This effect was greater than that observed previously in the spleen and liver after the injection of free ampicillin (9) and was more pronounced in the spleen than that observed previously after treatment with ampicillin bound to PIHCA nanoparticles (9). Our liposomal preparation was also more effective than the preparation described by others (2), which, in the same experimental model, had no effect on bacterial counts, presumably, as stated above, because a smaller amount of liposome-entrapped ampicillin was injected into the mice (2 doses of 0.27 mg each versus 3 doses of 0.8 mg each in the present study).…”
contrasting
confidence: 47%
“…We also showed with athymic nude mice that this linkage enhanced the effectiveness of ampicillin in treating chronic listeriosis (9), although Bakker-Woudenberg et al, who used liposome-entrapped ampicillin, observed no such enhancement (2). In their study, however, the dose of liposomeentrapped ampicillin injected was only 23% of the one we injected after linkage to nanoparticles (9).…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Regarding nanoparticles, ampicillin-containing polymeric nanoparticles were also significantly more effective than free ampicillin in a chronic experimental listeriosis in athymic nude mice (114). Seven days after the treatment administration, ampicillin-bound nanoparticles completely eradicated the infection in the liver, while free ampicillin did not ensure liver sterilization during the 19 days that the experiment lasted, even with doses as high as 48 mg (this total dosage was divided into three doses of 16 mg/each).…”
Section: Listeriosismentioning
confidence: 99%
“…This site specific or targeted delivery using specific ligands combined with delivery at an optimal rate would not only improve the efficacy of drug but would also reduce the possible unwanted side effects of drug thus improving the therapeutic index (13).…”
Section: Introductionmentioning
confidence: 99%